Where should generators be built in a zonal electricity market? A numerical analysis of administratively determined investment signals - Anselm Eicke (ZBW – Leibniz Information Centre for Economics, 2022)
The location of electricity generation assets within a power system involves a fundamental trade-off: is it better to place generators at sites where generation costs are low, or should generators be situated close to consumers? This question is particularly relevant for wind turbines and solar photovoltaics, whose availability strongly varies between regions. If market prices reflect network constraints, the prices provide a locational signal. This is not the case in zonal markets with uniform prices. There, regulators can intervene by other means, such as administratively determined network tariffs that vary by location and are paid by generators. In this work, I examine such regulatory locational instruments using a novel bi-level electricity market model. In the first stage, the regulator determines a locational signal. In the second stage, generators decide on investment and dispatch while accounting for the regulatory signal and the zonal electricity price. For an exemplary network, I find that the introduction of regulatory locational instruments significantly lowers the cost of electricity supply.
Keywords: 330; Locational signals; Investment incentives; OR in energy